Thousand Hands Bodhisattva: Aesthetics, Affect, Sensational Disability - Gao, Weisong (Disability Studies Quarterly, 2017)
This project examines the performance Thousand Hands Bodhisattva by hearing impaired dancers and the ways in which the invisible disability might provoke divergent viewing experiences and feelings contingent upon how the performance is contextualized. This performance showcases formal dancing techniques to elicit the sensation of beauty and the valorization of virtuosity, the presumed spectating responses to the aesthetic value of the performance. However, if the external knowledge of the dancers' disability is prefigured to the spectators, the contextualized performance would stir unexpected responses among the viewers, such as a feeling of shame, admiration and so on, because their taken-for-granted assumptions are challenged that beauty is unquestionably associated with completeness, wholeness, and ability, and that disabled individuals are radically less self-sufficient than the able-bodied. Eventually, I attempt to argue that this performance exemplifies a certain type of queer formalism because, by simultaneously sticking with the conventional form of dance while mobilizing the sensation of disability to queer the viewing experience, it disrupts the presupposed, normative and predictable relationship between an artistic form and its reception.